Effect of local vitamin E versus local dexamethasone on prevention of myringosclerosis - Mandour, Yasser Mohammad Hassan; Elsayed, Mohamed (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The objective of the study was to compare between effect of local vitamin E and local dexamethasone on prevention of myringosclerosis induced by ventilation tube in human tympanic membranes. Methods: 90 children undergoing myringotomy with ventilation tube insertion were divided into 3 groups: group-I: 30 children undergoing myringotomy with ventilation tube insertion only, group-II: 30 children under- going myringotomy with ventilation tube insertion with use of local vit E, group-III: 30 children under going myringotomy with ventilation tube insertion with use of local dexamethasone. Results: The incidence of myringosclerosis occurance with otoscopic and microscopic examination was lesser in group 2 (6 ears) in which local vit E was applied than group 3 (11 ears) in which local dexamethasone was applied and also than group1 in which no local medication was applied (21 ears). Conclusions: In this study results suggest that applying local vit E in children under going myringotomy with ventilation tube insertion more effective than use of local dexamethasone in children undergoing myringotomy with ventilation tube insertion on limiting the intensity and prevalence of myringosclerosis.